(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This paper has made a study of the Indian capital markets together with analyzing their role in the growth process of the economy. Starting with a survey of literature on the importance of these markets in the process of economic growth, this paper brings to the fore in what way the reforms undertaken in the financial sector as part of the liberalization package of the early nineties have transformed them. Specifically, the situation concerning size, liquidity, and volatility has been studied, together with various qualitative aspects of the transformation. The paper further examines with the help of vector autoregressive and the vector error correction models as to what extent these markets have played a catalytic role in India’s growth process in the post-reform period. It has also examined whether their role is complementary to that of the financial institutions or do the two stand in competition to each other.